In-Silico Evaluation of Binding Interaction and ADME Properties of Novel Pyrazoline and Pyrimidine Derivatives Targeting Cyclooxygenase-2 Enzyme (Al Mustansiriyah Journal of Pharmaceutical Sciences, 2025)
Inflammation is a crucial defense mechanism against toxic stimuli and physical traumas. This study aimed to design six new pyrazoline and pyrimidine derivatives and assess their potential anti-inflammatory activity by targeting the cyclooxygenase (COX) enzyme, a key mediator in the inflammation process. Through in-silico methods, the binding affinity of these derivatives to the COX-2 receptor was predicted using computer simulations and compared with the reference drug, meloxicam.Docking studies employing gold software facilitated the visualization of ligand-protein interactions, utilizing the crystal structure of the COX-2 protein (PDB ID: 4m11). Preceding the docking procedure, the receptor underwent energy minimization by SPDPV software and hydrogen atoms addition. Compounds 1 to 6 exhibited superior docking scores, indicative of strong binding affinities and favorable positioning within the COX-2 enzyme's active site. The results of using this approach are series of products content of pyrazoline and pyrimidine derivatives that had greater potency as anti-inflammatory action and binding in the active location inside the COX-2 protein may potentially serve as a lead for the identification of novel anti-inflammatory medications to decrease the side effects and toxicity that produced from some NSAIDs.